Genetic Regulation of Vertebrate Forebrain Development by Homeobox Genes - Leung, Ryan F.; George, Ankita M.; Roussel, Enola M.; Faux, Maree C.; Wigle, Jeffrey T.; Eisenstat, David D. (Frontiers in Neuroscience, 2022)
Forebrain development in vertebrates is regulated by transcription factors encoded by homeobox, bHLH and forkhead gene families throughout the progressive and overlapping stages of neural induction and patterning, regional specification and generation of neurons and glia from central nervous system (CNS) progenitor cells. Moreover, cell fate decisions, differentiation and migration of these committed CNS progenitors are controlled by the gene regulatory networks that are regulated by various homeodomain-containing transcription factors, including but not limited to those of the Pax (paired), Nkx, Otx (orthodenticle), Gsx/Gsh (genetic screened) and Dlx (distal-less) homeobox gene families. This comprehensive review outlines the integral role of key homeobox transcription factors and their target genes on forebrain development, focused primarily on the telencephalon. Furthermore, links of these transcription factors to human diseases, such as neurodevelopmental disorders and brain tumours are provided.